(untitled) (Academia Science Repository, 2023)
Today there is a huge number of techniques and guidelines for teachers on the organization of the educational process. However, in our opinion, little attention is paid to the use of public relations (PR) technologies in education. Currently, PR is a sophisticated area that is rich in various specialists; but, as a rule, their attention is directed towards the promotion of goods, services, and media celebrities. The article discusses the usage of PR techniques in the educational process.